Using cluster analysis for the study of generation Y behavior at the University of Pardubice - Jonášová, Hana; Michálek, Karel; Panuš, Jan (Univerzita Pardubice, 2012)
For Generation Y are social networks an essential element ofcommunication and entertainment. The authors of this article conducted research in the Faculty of Economics and Administration at the University of Pardubice on howstudents (generation Y) use social networks. For the evaluation of research were usedcluster analysis and decision trees.
Keywords: generation Y; social network; Faculty of Economics and Administration University of Pardubice; Facebook; communication; questionnaire survey; cluster analysis; kohonen self-organizing feature maps; k-means; two-step; C5.0; decision trees